Application of Perovskite Strontium Doped Neodymium Manganite (Nd0.6Sr0.4MnO3) for Effective Removal of Fast Green Dye, A Toxic Wastewater Contaminant". Issue 13 (3rd April 2023) - Bhoriya, Ankit; Sachin; Bura, Neha; Yadav, Deepa; Singh, Jasveer; Singh, Nahar; Singh, H. K.; Dilawar Sharma, Nita
Abstract: Water is a natural and universal solvent that sustains life on earth. Due to industrialisation, pure water resources are exposed to contamination at an alarming rate due to various organic and inorganic substances. Dyes, with organic contaminants in particular, are very harmful to human and aquatic life due to their carcinogenic nature. The primary consumers of dyes are the textiles and printing industries which release wastewater with high concentrations of these dyes. Therefore, severe measures are needed to remove dye from wastewater. Herein, authors report a study, the first of its kind, to remove the organic contaminants, especially Fast Green dye, from wastewater using Strontium doped neodymium manganite, Nd0.6 Sr0.4 MnO3 (NSMO) as an adsorbent. The adsorbent NSMO was synthesized via a solid‐state reaction route. The structural and microstructural characterizations reveal that the samples are orthorhombic polycrystalline and have a dense growth of particles. To assess the efficacy of dye removal of NSMO, preliminary studies were carried out on the effects of pH variation, initial dye concentration, and contact time, followed by adsorption kinetic studies using dye in water as a contaminant. The isotherm and kinetic studies suggest that dye removal from wastewater follows the second‐order kinetics and Langmuir isotherm model. It was found that the maximum percentage removal for 100 mg/L of dye solution is close to 99 % using 0.05 g of adsorbent for 60 min. The novelty of the approach is brought out by the fact that, to date, only photocatalytic studies have been carried out on this material. Abstract : Solid state synthesized 40 % Sr doped manganite, one of the prominent members of perovskite family, has been employed successfully for adsorption based application for the removal of Fast Green dye from waste water. Different parameters are study to optimize the adsorption process.